2008
DOI: 10.1152/japplphysiol.01034.2007
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced attenuation of obesity, hyperinsulinemia, and skeletal muscle lipid peroxidation in the OLETF rat

Abstract: Morris RT, Laye MJ, Lees SJ, Rector RS, Thyfault JP, Booth FW. Exercise-induced attenuation of obesity, hyperinsulinemia, and skeletal muscle lipid peroxidation in the OLETF rat. J Appl Physiol 104: 708-715, 2008. First published December 13, 2007 doi:10.1152/japplphysiol.01034.2007.-The Otsuka Long-Evans Tokushima fatty (OLETF) rat is a model of hyperphagic obesity in which the animals retain the desire to run voluntarily. Running wheels were provided for 4-wk-old OLETF rats for 16 wk before they were killed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 57 publications
(60 reference statements)
5
36
1
2
Order By: Relevance
“…2A). Similar to our previous reports (26,35), running animals displayed initial running distances of ϳ4 km/day at 4 wk of age and 12 km/day at 9 -10 wk of age and averaging 5-8 km/day for the remainder of the study (weeks 10 -20). The health benefits of daily physical activity were lower body weight, body fat percentage, and fat pad mass (omental and retroperitoneal) in the OLETF-WL5hr (P Ͻ 0.05; see Fig.…”
Section: Resultssupporting
confidence: 89%
“…2A). Similar to our previous reports (26,35), running animals displayed initial running distances of ϳ4 km/day at 4 wk of age and 12 km/day at 9 -10 wk of age and averaging 5-8 km/day for the remainder of the study (weeks 10 -20). The health benefits of daily physical activity were lower body weight, body fat percentage, and fat pad mass (omental and retroperitoneal) in the OLETF-WL5hr (P Ͻ 0.05; see Fig.…”
Section: Resultssupporting
confidence: 89%
“…Similar to what we have reported previously (19,21), initial running distance at 4 wk of age averaged ϳ5 km/day (ϳ170 min/day, ϳ33 m/min), with daily distances peaking between 8 and 11 wk of age (ϳ11-12 km/day, ϳ275 min/day, ϳ43 m/min) and declining to ϳ6 -8 km/day (ϳ200 min/day, ϳ32 m/min) at 20 wk of age, and ϳ4 km/day (ϳ150 min/day, ϳ27 m/min) by 40 wk of age in the OLETF-EX rats. It remains unknown why the OLETF animals exhibited decreased voluntary wheel running as they aged, but perhaps the OLETFs appropriately mirror the human condition, in which aging is often associated with reduced physical activity.…”
Section: Animal Characteristicssupporting
confidence: 92%
“…We have previously shown that 16 wk of daily voluntary exercise in the OLETF rat was associated with lower levels of lipid peroxidation without significant changes in intramyocellular lipids (21). In the current report, OLETF-SED rats exhibited increases in SOD and catalase activity from 20 to 40 wk when the health of the animal deteriorated, changes not witnessed in OLETF-EX and LETO-SED rats.…”
Section: Discussionsupporting
confidence: 45%
“…In obese mice roughly 7% of the AFABP in adipose tissue is covalently modified by HNE resulting in a decreased binding affinity for fatty acids. Lipid peroxidation is however not restricted to adipose tissue since HNE is also elevated in skeletal muscles of Otsuka Long-Evans Tokushima fatty (OLETF) rat, a model for hyperphagic obesity (Morris et al, 2008). Intracellular triglyacylglycerols accumulate in the muscle of obese humans where it is considered as a pathogenic factor in the development of insulin resistance.…”
Section: Lipid Peroxidation By-products Association With Obesitymentioning
confidence: 99%